CENTRAL ASIAN REGION AT THE FOCUS OF GEOPOLITICAL INTERESTS - Ayupova Z.K.; Kussainov D.U.; Beisenbayeva M.T.; Winston Nagan (Scientific Journal of Pedagogy and Economics, 2020)
In the XXI century the role of Central Asia in international politics is increasing. This region, possessing rich natural, energy, mineral and raw material resources, has an important geostrategic position, in which we see the geopolitical confrontation of global actors. The confrontation is explained by the fact that, for example, for Russia this region, being a “vulnerable underbelly”, is included in the traditional sphere of influence, from the perspective of China, the region seems to be an alternative source of energy and a vital partner for stabilizing and developing the troubled Xinjiang province. As for the United States and their allies, this region appears to be an important transportation hub, for example, for military supplies to unstable Afghanistan. Central Asia is not only a key region on the world map, the establishment of control over which allows you to manage the regional transit of hydrocarbons and other types of strategic raw materials for the largest developing economies, primarily China, and, as a result, affect their economic growth and aggregate power. Central Asia is a crossroad of civilizations, control over which, as was believed over the centuries, allows you to rule the world. The region retains its exceptional geopolitical significance today.